2015
DOI: 10.1111/jsm.12932
|View full text |Cite
|
Sign up to set email alerts
|

Penile Prosthesis First and Replacement Surgeries: Analysis of Patient and Partner Satisfaction

Abstract: Introduction Among the many treatments for erectile dysfunction, implantation of a penile prosthesis has been associated with high patient satisfaction rates. Prosthesis replacement has become an accepted procedure in the event of device malfunction or complications, but to our knowledge, there are no data regarding the impact of implant replacement on patients and partner satisfaction. Aim The aim of our study was to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Grewal et al surveyed patients discharge and re‐visit data in a contemporary series of penile implant surgeries and found that infectious complications were the most common reason for reoperation. Whilst Lledó‐García et al reported high patient and partner satisfaction after both primary and replacement surgery. Reoperation is an undesirable event as it is associated not only with added morbidity but also with inferior results, including reduced implant survival.…”
Section: Discussionmentioning
confidence: 99%
“…Grewal et al surveyed patients discharge and re‐visit data in a contemporary series of penile implant surgeries and found that infectious complications were the most common reason for reoperation. Whilst Lledó‐García et al reported high patient and partner satisfaction after both primary and replacement surgery. Reoperation is an undesirable event as it is associated not only with added morbidity but also with inferior results, including reduced implant survival.…”
Section: Discussionmentioning
confidence: 99%
“…The inflatable penile prosthesis (IPP) has become the standard of care for severe erectile dysfunction refractory to non-surgical therapies. IPP placement is a reliable, safe surgical treatment option with high patient satisfaction rates [1][2][3]. The use of Rear Tip Extenders (RTEs) is an underexplored aspect of IPP placement.…”
Section: Introductionmentioning
confidence: 99%
“…The inflatable penile prosthesis (IPP) has evolved over the past four decades and become a reliable, safe surgical treatment option with high patient satisfaction rates [13]. Rear Tip Extenders (RTEs) were introduced in 1981 [4], in an effort to decrease input wear on the cylinders.…”
Section: Introductionmentioning
confidence: 99%